Menstrual hygiene practices among rural adolescent girls in a north Karnataka village: a cross-sectional study - Daniel, Rachel Sushmita; Todalabagi, Pooja (International Journal Of Community Medicine And Public Health, 2025)
Background: Menstrual hygiene management (MHM) is vital for adolescent girls' health and participation in education and society. However, rural girls face unique challenges due to cultural taboos, poor infrastructure, and limited access to menstrual products. This study aimed to assess the menstrual hygiene practices of adolescent girls in Ukkali village, Karnataka, and identify factors influencing their behaviors and social restrictions during menstruation. Methods: A cross-sectional study was conducted among 280 school-going adolescent girls aged 12-17 years in Ukkali village, Karnataka, from September to October 2024. Participants were selected using systematic random sampling across six schools. Data were collected through a validated self-administered menstrual hygiene questionnaire and analyzed using SPSS version 26. Results: The mean age of participants was 13.9 years, with a mean age of menarche of 12.85 years. Most participants (75%) used disposable sanitary pads, 22.5% relied on cloth, and 26.4% reused materials. Hygiene practices were suboptimal, with only 35.7% washing genitals once daily and 6.1% washing only at the end of their period. Social restrictions during menstruation included avoiding places of worship (39.3%) and discontinuing physical exercise (28.6%). Significant associations were observed between menstrual flow and restrictions (p=0.010) and between genital washing frequency and restrictions (p<0.001). Conclusions: Suboptimal menstrual hygiene practices and restrictive social norms persist among rural adolescent girls in Ukkali village. Comprehensive strategies, including education, enhanced access to menstrual products, and improved infrastructure, are essential to promote health, dignity, and gender equality.